INCREASING STUDENTS’ LEARNING OUTCOMES THROUGH STUDENT TEAMS ACHIEVEMENT DIVISION (STAD) MODEL AT GRADE V SD - Desi Endang K. Sitepu; Patri Janson Silaban; ,Saut Mahulae (Laboratorium Program Studi Pendidikan Guru Sekolah Dasar, 2021)
This study aimed to improve students’ learning outcomes through Student Teams Achievement Division (STAD) Model. This study was Classroom Action Research (CAR). The subjects of this study were 30 fifth grade students of SD Negeri 067246 Medan Tuntungan. The results in the pretest showed that 5 students reached the KKM, classically was 16.66% with an average score of 54.02. In cycle I, 11 students reached the KKM, classically was 36.66% with an average of 68.72. In cycle II, 27 students reached the KKM, classically was 82.55% with an average of 82.55. Learning through Student Teams Achievement Division (STAD) model was categorized as very good. This was seen from the results of observations of teacher activities in cycle I which was 72% and in cycle II it increased to 86%. The implementation of learning was categorized as good. This was seen from the observation results of students’ activities in cycle I which was 70% and in cycle II it increased to 82%. Thus, implementing Student Teams Achievement Division (STAD) model improved students’ learning outcomes on the ecosystem theme.